The relationship between the consumption of different types of alcoholic beverages and household income inequality - Gavurová, Beáta; Oláh, Judit; Rigelský, Martin; Ivanková, Viera (Adiktologie, 2020)
BACKGROUND: The relationship between the consumption of alcoholic beverages and the economic outputs of countries is generally perceived negatively. Recent studies suggest that there is a difference in the effect of different types of alcohol on economic outputs. AIMS: The objective of the present study was to evaluate the relations between alcohol consumption and household income inequality in OECD countries, with a primary focus on selected types of alcoholic beverages. METHODS: In order to achieve this objective, a non-parametric analysis of relationships (Spearman ρ) and a regression analysis (Instrumental Variables Estimator – Two-Stage Least Squares Regression Analysis) were used. SAMPLE: The countries of the OECD were included in the analyses. The analytical focus was on three dominant types of alcoholic beverages: beer, wine, spirits. Alcohol consumption was expressed in litres of pure alcohol per person over the age of 15 in each country. RESULTS: In OECD countries, beer is the most preferred alcoholic beverage, followed by wine, and spirits are the least preferred. The consumption of beer and wine was significantly related to the Gini coefficient. Thus, an increase in the consumption of beer or wine can be associated with a decrease in the Gini coefficient. In terms of the effects of individual alcoholic beverages on inequality in household income, wine was evaluated most positively, as its increased consumption can lead to a reduction in household income inequality. Spirits had the opposite effect; i.e. increased consumption may increase household income inequality. CONCLUSIONS: Prevention and education should focus on reducing the consumption of spirits, and fiscal interventions such as taxes can also be an effective solution. Alcohol consumption is a cultural aspect that is difficult to eliminate. Therefore, it would be more beneficial to replace spirits with wine.